FASTING LIPID PROFILE AND ITS ASSOCIATION WITH THE RISK OF DIABETIC FOOT ULCERS IN TYPE 2 DIABETES MELLITUS. : J Peop Univ Med Health Sci. 2025:15(3), 23-29. http://doi.org/10.46536/jpumhs/2025/15.03.654 - Saleem Ullah Abro1, Qurratulain Saleem2, Jamal Ara Fasih3, Jahanzaib Lashari4, Mohammad Ali5, Viny Kumar6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Diabetic foot ulcer is the leading micrcirculatory complication of type 2 diabetes mellitus (T2DM) and is considered a significant factor leading to lower limb amputation. Objective: To evaluate the fasting lipid profile and its association with the risk of diabetic foot ulcers in individuals with T2DM. METHODS: A comparative cross-sectional study was carried out at Baqai Medical University from June 2023 to 2024. A total of 138 participants were grouped into healthy controls, T2DM, and foot ulcer in diabetic patients, enrolled via convenience sampling. The median values of three groups were analyzed using one-way ANOVA technique and the Kruskal- Wallis test for parameters that were not normally distributed. Post hoc analysis was performed with Dunnett’s T3 test for variables with significant (p<0.05) differences, and risk assessment was conducted based on 95% confidence intervals and odds ratio. SPSS version 23 was used for gathering and evaluating the data. RESULTS: The median fasting lipid profiles differed significantly among the three groups (p<0.01). Low-density lipoproteins (LDL), triglycerides (TG), and very low-density lipoproteins (VLDL) did not show significant differences (p>0.05) among the all three groups, according to Dunnett’s T3 test for multiple comparisons. However, significant association (p<0.05) existed between cholesterol and HDL levels. Among these parameters TG, HDL, and VLDL were significantly associated with risk in T2DM, and serum cholesterol, TG, HDL, LDL, and VLDL showed significant risk association for DFUs with p<0.05 by using Multinomial Logistic Regression. CONCLUSION: The results of this research showed a significant association of fasting lipid profile components (TG, HDL, VLDL) with T2DM, and plasma fat, TG, HDL, LDL, and VLDL with DFUs.